Kesejahteraan Karyawan PT. Royal Coconut Kabupaten Minahasa Utara - Karim, Dian Fitriani; Kaunang, Markus; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
Employee welfare is a form of welfare services provided by the company to the employees who have given power, mind and their services. Company Parties have an obligation to make efforts to motivate employees to provide benefits that can improve employee productivity. Welfare programs provided by the company to employees of PT. Royal Coconut North Minahasa yet either. Using qualitative methodology, research results show that the well-being of employees is not a good idea due to the PT. Royal Coconut not impose the maximum employee welfare services in terms of economic, facilities, and welfare services. Key Words: werlfare, imployee, economis, service, and facility